An Acoustic Analysis of Word Stress Production by Indonesian Learners of English - Nurpahmi, Sitti; Muthi'ah, Muthi'ah; Nur, Nur Aliyah; Basrun, Aldrianti Dinar (Institut Agama Islam Negeri Palopo, 2023)
: Although word stress is a crucial aspect of English speaking, it is not given much emphasis in Indonesia's EFL instruction. Students, consequently, lack the theoretical understanding of how to properly stress syllables in English words. This study uses a program named Praat to examine the acoustic parameters of word stress produced by EFL students in terms of its intensity level. These parameters can indicate whether the students pronounce two-syllable words of nouns and verbs accurately. The subjects of this research were the third-year students of English Education Department who were selected purposively based on the students’ results of EF SET (Standardized English Test). The findings revealed that the students produced more inaccurate word stress when pronouncing nouns than they did when pronouncing verbs. Moreover, the inaccurate word stress produced by the students was divided into three categories: equation stress, no-stress placement, and reverse stress. Among the three categories, equation stress is the most common error found in this study. This study provides insight into the features of word stress and the acoustic measurement of word stress produced by Indonesian learners of English. It implies that there is a need to integrate explicit instruction on word stress. This could involve dedicated lessons on stress placement, incorporating practical exercises and feedback mechanisms to help students develop a theoretical understanding and practical skills in pronouncing English words accurately. The study also encourages future research in related areas, suggesting a focus on other pronunciation problems like intonation. This broader approach to research can contribute to a more comprehensive understanding of the challenges Indonesian learners face in mastering English pronunciation that can provide a foundation for curriculum development and instructional strategies aimed at enhancing English language proficiency in Indonesia.